The subjective assessment of freshmen's health issues at the Faculty of humanities and Social Sciences in Zagreb - Gošnik, Jelka (2012)
Croatian study programs according to the Bologna principles follow the contemporary European trends in higher education, which seek to create and maintain its quality. This means that the set tasks are becoming more demanding and harder to fulfill, which increases the threat to the bio-psycho-affective state of freshmen during their study. This paper investigates whether and to what extent freshmen have health problems, and whether and how the higher education system with its mandatory program of physical education may help to improve their health status. In the academic year 2011/2012 we conducted a non-anonymous survey on a sample of 745 informants, examining one variable with 20 subvariables. The subvariables refer to the subjective assessment of health status of examinees at the Faculty of Humanities and Social Sciences in Zagreb. The examinees have assessed the seriousness of their own health issues on the Likert scale. The collected data were processed using the statistical package Statistica 7.0. The results indicate that the level of health problems of freshmen is increased in 5 variables: Allergies, Eye Disease, Insomnia, Lack of Energy, and Headaches and Migraines. Spine and circulation problems together with low blood pressure are usually found in the range of 10% to 20%, while other health issues were determined in less than 10% of the total student population. The results also show the existence of threats to psychosomatic state of freshmen, which may be the consequence of a sedentary lifestyle and work on computers. Health risks manifest themselves with harmful effects on vision, disorders related to stress and fatigue, and workload of the musculoskeletal system. The central role in this situation have physical education programs that the Faculty offers, the motivation of teachers, and the strategic backdrop of Kinesiology curriculum, applied with the aim of turning young people towards a healthy lifestyle.